Visual Outcomes of Cataract Surgery at a Tertiary Care Hospital in Northern Sri Lanka - Malaravan, M.; Kumaran, S.; Kumanan, T.; Aruljenani, K.; Powsiga, U.; Thurga, J. (Cureus, 2026)
Background: Cataract is the leading cause of blindness and visual impairment. Cataract surgery is the most common procedure for restoring vision in individuals with cataracts. It is important to assess the surgical outcomes of cataract surgery to ensure the highest standard of vision restoration, improved patient quality of life, and service delivery. Therefore, the present study aimed to evaluate the visual outcomes of cataract surgery among patients attending the Eye Unit of Teaching Hospital Jaffna, Northern Sri Lanka, at the fourth week follow-up postoperatively. Methods: An institution-based, retrospective analytical study design was conducted among 1,133 patients who underwent cataract surgery using phacoemulsification with intraocular lens implantation. The study participants were selected using a systematic random sampling technique. Data were obtained through a structured data extraction form derived from patients’ medical records and an interviewer-administered questionnaire, and were subsequently analysed using IBM SPSS Statistics for Windows, Version 25 (Released 2017; IBM Corp., Armonk, New York, United States). Proportions, summary statistics, and tables were used to present the findings. Multivariable linear regression was performed to identify associations among the variables. A p‑value of <0.05 was considered indicative of statistical significance. Results: Among 1,133 patients who underwent phacoemulsification with intraocular lens implantation, 1,027 (90.6%) achieved good postoperative visual outcomes of 6/12 or better. The majority, 699 (61.7%), were female, and 800 (70.6%) were aged 60 years and above. The most common systemic comorbidities were hypertension with 386 (34.1%) patients and diabetes mellitus with 350 (30.9%), while 24 (2.1%) of them had pre-existing ocular comorbidities. Patients aged 60 years and above demonstrated significantly less improvement in visual acuity than those aged <60 years (p < 0.001). Diabetes mellitus was independently associated with reduced postoperative visual improvement (p = 0.014), whereas sex and pre-existing ocular comorbidities were not. Conclusion: The visual outcome following cataract surgery exceeds WHO recommendations. In this study, age and diabetes mellitus were associated with postoperative visual outcomes, whereas the presence of other ocular comorbidities and sex were not. Furthermore, this study demonstrates that good postoperative visual outcomes can be achieved with cataract surgery even in resource-constrained settings.
Keywords: Best corrected visual acuity (bcva); Cataract; Low and middle-income countries; Northern sri lanka; Phacoemulsification cataract surgery; Post operative outcomes; Postoperative visual outcome; World health organization (who)